2011
DOI: 10.1021/jp1096037
|View full text |Cite
|
Sign up to set email alerts
|

Electrode-Supported Biomembrane for Examining Electron-Transfer and Ion-Transfer Reactions of Encapsulated Low Molecular Weight Biological Molecules

Abstract: A robust model membrane environment has been developed to enable voltammetry experiments to be performed on low molecular weight biological molecules completely incorporated inside artificial lipid bilayer (or multilayer) membranes. The artificial supported membranes were prepared by sandwiching multilayers of lecithin between layers of Nafion that were deposited on the surface of a glassy carbon electrode. The Nafion films acted as a conduit to aid proton transfer across the lecithin solution interface, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 102 publications
1
30
0
Order By: Relevance
“…Cyclic voltammetry applied to Hg-supported tBLMs [11,12] is a powerful and versatile electrochemical technique, since it may also monitor the effect of a change in the rate of ion flow upon the current by varying the potential scan rate. It should be noted that applications of cyclic voltammetry to biomimetic membranes have been so far confined to the electron transfer across the lipid bilayer mediated by some redox couple [50,51], and not extended to the translocation of inorganic ions of biological interest, with only some exceptions at BLMs [46,47,52].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic voltammetry applied to Hg-supported tBLMs [11,12] is a powerful and versatile electrochemical technique, since it may also monitor the effect of a change in the rate of ion flow upon the current by varying the potential scan rate. It should be noted that applications of cyclic voltammetry to biomimetic membranes have been so far confined to the electron transfer across the lipid bilayer mediated by some redox couple [50,51], and not extended to the translocation of inorganic ions of biological interest, with only some exceptions at BLMs [46,47,52].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of hydrophobic electroactive molecules in lipid bilayers also allows testing electrode reactions in a biomimetic environment [23][24][25]. The interactions of the generated redox products with the surroundings can lead to the design of sensors based on supported electroactive lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…In a previously reported micellar solution of 1 , the reduction process did show a pH dependence on the peak potentials and currents . This is in contrast with our finding, which indicates that the membrane environment of the vesicles under study provides a constant local effective pH to the catalyst, as observed previously in similar lipid bilayers …”
Section: Resultsmentioning
confidence: 99%
“…[38] This is in contrastw ith our finding, which indicates that the membrane environmento ft he vesicles under study provides ac onstant local effective pH to the catalyst, as observed previously in similar lipid bilayers. [39] During electrochemical measurements, vesicles appeared to be adsorbed onto the glassy carbon working electrode. This was demonstrated by removing the electrode from the solution after af ew scans, rinsing with deionized water,a nd submerging in fresh buffer solution, after which similar voltammograms were recorded.…”
Section: Electrochemistrymentioning
confidence: 99%